The Importance of the Development of Eco-innovations in the Transformation to a Green Economy - Halyna Matviienko; Матвієнко Галина; Matvijenkó G.; Kucherkova Svitlana; Кучеркова Світлана; Kucserkova Sz. (II. Rákóczi Ferenc Kárpátaljai Magyar Főiskola, 2024)
Abstract. The article is devoted to the importance of the development of eco-innovations in the transformation to a green economy. The importance of the green economy and eco-innovations for future development is determined. The relationship between technology and sustainable development is proven. The classification of eco-innovations and eco-innovators is presented. The main climate risks and economic losses from them in Europe have been identified. Sustainability actions taken by enterprises in the EU are defined. Defined the state of innovation activity of enterprises as a basis for the development of green innovation. Proposed ways to stimulate the development of eco-innovations, with the definition of the main actions at the micro and macro levels and a proposed scheme of ecoinnovation system. The purpose of the article is determining the economic risks of global climate change and their neutralization and mitigation through the use of eco-innovations. Justification of the positive synergistic effect of eco-innovations on economic indicators, the standard of living and sustainable development is provided. The article used research and analytical articles, studies of scientists and world economic organizations: the World Bank Group, IMF, UN and others. Materials of specific organizations and the European Commission were used. The main research methods were scientific abstraction, logical generalization when determining the need for green innovations at the current stage of development; analytical method for determining the components of the policy of eco-innovation and their interrelationships; a visual reflection of the sustainable eco-innovation system in the EU; situational analysis to identify problems of energy system. System-structural analysis - for the development of a conceptual model of eco-innovation policy, a structural-logical scheme of the formation of the main elements of the eco-innovation policy; complex empirical and applied analysis - to determine challenges, directions for green transformation and development of eco-innovations.

Резюме. Стаття присвячена значенню розвитку екоінновацій у трансформації до зеленої економіки. Визначено важливість зеленої економіки та екоінновацій для майбутнього розвитку. Доведено взаємозв’язок між технологією та сталим розвитком. Подано класифікацію екоінновацій та екоінноваторів. Визначено основні кліматичні ризики та економічні втрати від них у Європі. Визначено заходи сталого розвитку, які вживають підприємства в ЄС. Визначено стан інноваційної активності підприємств як основу для розвитку зелених інновацій. Запропоновані шляхи стимулювання розвитку екоінновацій з визначенням основних дій на мікро- та макрорівнях та запропонована схема системи екоінновацій. Метою статті є визначення економічних ризиків глобальної зміни клімату та їх нейтралізація та пом’якшення шляхом використання екоінновацій. Обґрунтовано позитивний синергетичний ефект екоінновацій на економічні показники, рівень життя та сталий розвиток. У статті використано науково-аналітичні статті, дослідження науковців та світових економічних організацій: Групи Світового банку, МВФ, ООН та ін. Використано матеріали окремих організацій та Європейської комісії. Основними методами дослідження були наукова абстракція, логічне узагальнення при визначенні необхідності зелених інновацій на сучасному етапі розвитку; аналітичний метод визначення складових екоінноваційної політики та їх взаємозв'язку; візуальне відображення сталої еко-інноваційної системи в ЄС; ситуаційний аналіз для визначення проблем енергетичної системи. Системно-структурний аналіз – для розробки концептуальної моделі екоінноваційної політики, структурно-логічної схеми формування основних елементів екоінноваційної політики ; комплексний емпіричний та прикладний аналіз - для визначення викликів, напрямків зеленої трансформації та розвитку екоінновацій.

A cikk az ökoinnovációk fejlesztésének fontosságával foglalkozik a zöld gazdaságra való átállásban. Meghatározásra került a zöld gazdaság és az ökoinnovációk fontossága a jövőbeli fejlődés szempontjából. Bizonyításra került a technológia és a fenntartható fejlődés kapcsolata. Bemutatásra került az ökoinnovációk és ökoinnovátorok osztályozása. Meghatároztuk a fő éghajlati kockázatokat és az ezekből származó gazdasági veszteségeket Európában. Meghatároztuk az EU-ban a vállalkozások által alkalmazott fenntartható fejlődés intézkedéseit. A zöld innovációk fejlesztésének lehetőségeként a vállalkozások innovációs tevékenységének állapotát vettük alapul. Az ökoinnovációk fejlesztésének ösztönzéséhez mikro- és makroszintű lépések meghatározását végeztük el, valamint az ökoinnovációs rendszer jobb működéséhez agy sémát dolgoztunk ki. A cikk célja, hogy meghatározza a globális klímaváltozás gazdasági kockázatait, valamint azok semlegesítését, mérséklését az ökoinnovációk segítségével. Bizonyított az ökoinnovációk pozitív szinergikus hatása a gazdasági mutatókra, az életszínvonalra és a fenntartható fejlődésre. A cikk tudományos és elemző cikkeket, tudósok és globális gazdasági szervezetek kutatásait használja fel: a Világbankét, az IMF-ét, az ENSZét stb. valamint egyes szervezetek és az Európai Bizottság anyagait. A főb felhasznált kutatási módszerek között a tudományos absztrakció, a logikai általánosítás volt a zöld innovációk szükségességének meghatározására a fejlődés jelenlegi szakaszában; az ökoinnovációs politika összetevőinek és azok összefüggéseinek meghatározásának analitikus módszere; egy fenntartható ökoinnovációs rendszer vizuális megjelenítése az EU-ban; helyzetelemzés az energiarendszeri problémák azonosítására. Rendszer-strukturális elemzés - az ökoinnovációs politika koncepcionális modelljének, az ökoinnovációs politika fő elemeinek kialakításának strukturális-logikai sémájához; komplex empirikus és alkalmazott elemzés módszere - a kihívások, a zöld átalakulás és az ökoinnovációk fejlesztésének irányainak azonosítására.
Значення розвитку екоінновацій при переході до зеленої економіки
Az ökoinnovációk fejlesztésének jelentősége a zöld gazdaságra való átállásban
Редакційна колегія: https://aab-economics.kmf.uz.ua/aabe/about/editorialTeam
Зміст: https://aab-economics.kmf.uz.ua/aabe/issue/view/6
Keywords: climate change; eco-innovations; energy security; green economy; sustainable economy; economic risks